2011
DOI: 10.1128/aac.00424-11
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Fluconazole in Critically Ill Patients Receiving Continuous Venovenous Hemodiafiltration: Using Monte Carlo Simulations To Predict Doses for Specified Pharmacodynamic Targets

Abstract: Fluconazole is a widely used antifungal agent that is extensively reabsorbed in patients with normal renal function. However, its reabsorption can be compromised in patients with acute kidney injury, thereby leading to altered fluconazole clearance and total systemic exposure. Here, we explore the pharmacokinetics of fluconazole in 10 critically ill anuric patients receiving continuous venovenous hemodiafiltration (CVVHDF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…The results of the aforementioned study support the current study, which demonstrated that fluconazole at lower dosing failed to achieve the desired PK/PD in various scenarios. In a population PK study of fluconazole in critically ill patients receiving continuous veno-venous hemodiafiltration (CVVHDF), fluconazole clearance was higher than previously observed (32). Thus, this study recommended that higher fluconazole dosing is required in patients undergoing CVVHDF.…”
Section: Discussionmentioning
confidence: 83%
“…The results of the aforementioned study support the current study, which demonstrated that fluconazole at lower dosing failed to achieve the desired PK/PD in various scenarios. In a population PK study of fluconazole in critically ill patients receiving continuous veno-venous hemodiafiltration (CVVHDF), fluconazole clearance was higher than previously observed (32). Thus, this study recommended that higher fluconazole dosing is required in patients undergoing CVVHDF.…”
Section: Discussionmentioning
confidence: 83%
“…The possible exception to this conclusion is when ECMO is combined with hemofiltration or CVVHD. Studies in adults show that fluconazole CL increases in the presence of hemofiltration and CVVHD (26)(27)(28)(29). Only 5 children received hemofiltration, and two received CVVHD, limiting our ability to draw conclusions about their impact on CL.…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, critically ill patients requiring RRTs require higher doses of antibiotic than recommended for individuals receiving intermittent hemodialysis for end-stage renal disease (13,23,24). A pharmacokinetic study of ertapenem in critically ill subjects requiring extended daily dialysis (blood and dialysate flow rates of 160 ml/min, treatment duration of 480 min) suggested that a dose of 1 g every 24 h, substantially higher than the manufacturer's suggested dosing for patients with creatinine clearance of Ïœ30 ml/min/1.73 m 2 (500 mg q24h) or receiving maintenance hemodialysis (500 mg within 6 h prior to hemodialysis, supplementary 150 mg following the hemodialysis session), is more appropriate to achieve bactericidal targets (1,25).…”
Section: Discussionmentioning
confidence: 99%